2021
DOI: 10.1186/s12955-021-01757-1
|View full text |Cite
|
Sign up to set email alerts
|

Intragenerational social mobility and self-rated oral health in the british cohort study

Abstract: Background Most studies on social mobility and oral health have focused on movement between generations (intergenerational mobility) rather than movement within an individual’s own lifetime (intragenerational mobility). The aim of this study was to investigate the association between intragenerational social mobility from early to middle adulthood and self-rated oral health. Methods This study used data from 6524 participants of the 1970 British Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…We found no evidence to support the dissociative theory. This is in accordance with previous studies from different countries with a range of outcomes that have not found strong directionless social mobility effects ( Jonsson et al, 2017 ; McLoughlin et al, 2023 ; Mohd Khairuddin, Bernabé, & Delgado-Angulo, 2021 ). We note that in proposing this hypothesis, Sorokin particularly emphasised the negative consequences of upward trajectories for mental health outcomes ( Sorokin, 1927 ).…”
Section: Discussionsupporting
confidence: 93%
“…We found no evidence to support the dissociative theory. This is in accordance with previous studies from different countries with a range of outcomes that have not found strong directionless social mobility effects ( Jonsson et al, 2017 ; McLoughlin et al, 2023 ; Mohd Khairuddin, Bernabé, & Delgado-Angulo, 2021 ). We note that in proposing this hypothesis, Sorokin particularly emphasised the negative consequences of upward trajectories for mental health outcomes ( Sorokin, 1927 ).…”
Section: Discussionsupporting
confidence: 93%
“…The majority of respondents in this study (69.4%) reported perceiving their oral health as “very good”. A slightly higher proportion of individuals self-reporting “very good” oral health has been found in a self-reported oral health study from Germany [ 15 ] and in a British cohort study [ 18 ]. However, an even larger percentage (78.3%) in this study indicated that they considered their general health as “very good”.…”
Section: Discussionmentioning
confidence: 98%
“…As some authors have pointed out, a significant proportion of the adult population tends to seek dental care only in emergencies or when in pain, and considers routine dental visits either “unimportant” or “financially prohibitive” [ 12 , 13 , 14 ]. Studies have shown a clear association between advanced age, lower socioeconomic status, or educational level and self-rated poor oral health [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, most studies have used traditional regression methods that cannot disentangle the mobility effects per se from those of early‐ and later‐life socioeconomic position (SEP). Our group has recently addressed these challenges in relation to intragenerational mobility effects on oral health 4 …”
Section: Introductionmentioning
confidence: 99%
“…Our group has recently addressed these challenges in relation to intragenerational mobility effects on oral health. 4 Social mobility constitutes a central topic in sociology, with several theories proposed to understand its health effects. The classic dissociative thesis postulates that social mobility is a stressful experience for both upwardly and downwardly mobile individuals.…”
mentioning
confidence: 99%